Hydro-mechanical simulation and analysis of induced seismicity for a hydraulic stimulation test at the Reykjanes geothermal field, Iceland. (December 2021) - Keilegavlen, Eirik; Duboeuf, Laure; Dichiarante, Anna Maria; Halldórsdóttir, Sæunn; Stefansson, Ivar; Naumann, Marcel; Guðnason, Egill Árni; Ágústsson, Kristján; Eggertsson, Guðjón Helgi; Oye, Volker; Berre, Inga
Highlights: Modeling of injection-induced fault reactivation at Reykjanes, Iceland. 3D faulted reservoir model based on integration of different data types. Simulation of fully coupled hydro-mechanical processes and fault reactivation. Combined induced seismicity analysis and physics-based simulation. Improved understanding of interactions between faults in hydraulic stimulation. Abstract: The combination of seismic analysis with advanced physics-based simulation provides an opportunity to further understand injection-induced fault reactivation, including the hydro-mechanical interplay between different faults and the rock where they reside. Here, this is investigated based on data from hydraulic stimulation of a well at the Reykjanes geothermal field. Central is the development of an interdisciplinary framework for integration of different data types towards a 3D, hydro-mechanical and faulted geothermal reservoir simulation model. This work shows how seismic interpretations can improve simulation models and, reciprocally, how fully coupled physics-based modeling can add to seismic interpretations in analysis of fault reactivation. Graphical Abstract: Image, graphical abstract